Potret Kemiskinan dalam Novel Sandiwara Bumi Karya Taufiqurrahman Al-Azizy dan Implikasinya dalam Pembelajaran Teks Novel - Hamidah, Hamidah (Indonesian and Regional Language and Literature Department, Universitas Negeri Padang, 2023)
The purpose of this study is to describe the portrait of poverty in the novel Sandiwara Bumi by Taufiqurrahman al-Azizy using a mimetic approach. This type of research is qualitative research that uses descriptive methods. Qualitative research is research that has a research procedure using descriptive data in the form of written and spoken words from a person or perpetrator that can be observed. Portrait of poverty is a picture or painting in the form of exposure to the form of poverty. Poverty is the inability to meet basic needs so that they are less able to ensure the sustainability of life. The picture of poverty can be obtained from the author's speech, the speech or speech of the character, and the actions of the character contained in the novel Sandiwara Bumi by Taaufiqurrahman al-Azizy. Data collection techniques in this study are reading and understanding, giventarization, interpreting, califizing, and concluding data related to the portrait of poverty in the novel Sandiwara Bumi by Taufiqurrahman al-Azizy. The results of research found in the novel Sandiwara Bumi by Taufiqurrahman al-Azizy found a picture of poverty. The picture of poverty can be seen from several aspects. First, the forms of poverty which include: forms of absolute poverty and relative poverty. Second, factors that cause poverty include: limited natural resources, natural resources, uneven government policies and development, family burdens, and limited employment. Third, the consequences of poverty which include: crime, school dropout, and lack of basic necessities.